"Uma câmera para o povo": o vídeo digital como meio de representação do cotidiano por presidiários do Carandiru - Carlos Henrique Mendes Santiago (2006)
This work analyzes the consequences of the production of technical images for the knowledge of the daily life, understood as "life-world", concept developed by Schütz. Although Flusser considers that the technical images possess the potential totransform the knowledge (epistemology), as well as the models of behavior (ethics) and the experience (aesthetics) of the daily life, a cut is made and the technical images are analyzed here exclusively from the epistemological point of view. The analysis of the spatial, temporal and social arrangements made by Schütz allows the identification of the immutable aspects of the existence. These aspects are applied to the life-world construed intersubjectively by the prisoners of the Carandirus prison, in São Paulo, and described in utterings and images made by prisoners, employees, journalists, photographers and filmmakers. The images recorded by two prisonersand included in the documentary O prisioneiro da grade de ferro, by director Paulo Sacramento, are also analyzed. This analysis, based on the concepts of "technical image" and "symbolic forms", allows the perception of the categories used by the prisoners in the visual representation of the arrangements of their life-world. Produced with algorithms, that is, with an artificial language produced from a conscious reflection, the photograph, as well as the film and the video, is able to represent time as a quantitative concept, that may subsume the representations prevailed by the qualitative aspects of the conscience.